Preparation method of organic silicon quantum dot electron transport layer material and solar cell
Patent Information
- Application Number
- CN202310938978.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-07-27
AI Technical Summary
[0006]中国专利CN111799379A公开了包含有机硅量子点材料的太阳能电池及其制备方法,其根据文献(NanoLett.2018,18,1159-1167)报道的方法制备得到的超小有机硅量子点纳米材料OSiND制作电子传输层,虽然结合实验结果在加入超小有机硅量子点(OSiNDs)以后,有机聚合物太阳能器件的短路电流明显增加,有效减少了ZnO层的缺馅,但填充因子及转换效率并未见有明显提升,甚至还略有下降
[0025]S4、制备好空穴传输层后,在高真空度的热蒸发腔室中制备金属阳极层,得到所述的太阳能电池。
Smart Images

Figure CN116867294B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic photovoltaic device technology, specifically relating to a method for preparing an organosilicon quantum dot electron transport layer material and a solar cell containing the electron transport layer. Background Technology
[0002] Organic solar cells (OSCs) based on bulk heterojunctions (BHJs) of donor and acceptor materials have emerged as one of the most promising candidates for next-generation photovoltaic cells due to their low cost and ease of fabrication via solution processes. Furthermore, their mechanical flexibility and light weight make OSCs suitable for wearable and portable power sources. Moreover, thanks to the recent rapid development of non-fullerene acceptors (NFAs), OSCs have achieved high power conversion efficiencies (PCE) exceeding 19%.
[0003] In the development of organic solar cells, researchers have found that the degree of energy level matching between the active layer material and the metal electrode material is crucial to improving the performance of the device. Therefore, some researchers have proposed adding an intermediate layer between the active layer and the electrode to improve its energy level matching. This layer is called the interface modification layer or buffer layer. This layer usually includes an electron transport layer and a hole transport layer.
[0004] The choice of electron transport layer (ETL) is crucial for improving the cathode electrochemical efficiency (PCE) because the ETL enhances charge extraction from the BHJ layer to the metal electrode by reducing the energy barrier at the BHJ / electrode interface. It is well known that most organic interface materials are amino derivatives, including neutral amine derivatives and ammonium derivatives, which can reduce the work function of the cathode by forming interfacial dipoles. Examples include polyelectrolytes (PE) (e.g., polyethyleneimine (PEIE), PDINO, and PFN-Br) or metal oxides (MOs) (i.e., TiOx, SnO2, and ZnO). Some organic polymers such as PEN-Br, PDINN, and PDINO have also been shown to have good cathode interface modification capabilities, but they are prone to poor stability.
[0005] As excellent bioimaging probe materials, quantum dots possess extremely high biocompatibility, fluorescence stability, controllable emission wavelength, wide excitation wavelength range, low biotoxicity, and good solubility. These properties make them potentially applicable to the field of organic photovoltaic devices to improve battery performance, but research in this area is still relatively limited.
[0006] Chinese patent CN111799379A discloses a solar cell containing organosilicon quantum dot materials and its preparation method. The electron transport layer is prepared by ultra-small organosilicon quantum dot nanomaterials OSiND according to the method reported in the literature (NanoLett.2018, 18, 1159-1167). Although the experimental results show that the short-circuit current of the organic polymer solar device increases significantly after the addition of ultra-small organosilicon quantum dots (OSiNDs), effectively reducing the defect of the ZnO layer, the fill factor and conversion efficiency are not significantly improved, and even slightly decreased.
[0007] Therefore, the fabrication of electron transport layers using organosilicon quantum dot materials requires further optimization. Summary of the Invention
[0008] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention provides a method for preparing an organosilicon quantum dot electron transport layer material. When the obtained electron transport layer material is applied to a solar cell, not only does the short-circuit current of the device increase significantly, but the fill factor and conversion efficiency are also significantly improved.
[0009] In one aspect, the present invention provides a method for preparing an organosilicon quantum dot electron transport layer material, comprising the following steps: dissolving 3-aminopropyltrimethoxysilane (AEEA) in deionized water in a certain proportion, stirring and purging with nitrogen, performing hydrothermal treatment, and after the reaction is completed, naturally cooling to room temperature to obtain the organosilicon quantum dot electron transport layer material OSiNDs-AEEA.
[0010] The proposed method directly yields the organosilicon quantum dot electron transport layer material OSiNDs-AEEA through a hydrothermal reaction of AEEA under nitrogen conditions. The preparation method is simple and low-cost. The amino group of the terminal functional group of the obtained material—3-aminopropyltrimethoxysilane (AEEA)—ensures its good solubility in water. By passivating the adsorbed oxygen defects on the surface, the light immersion effect of the inverted organic solar cell can be effectively suppressed, which helps to improve the photoelectric conversion efficiency of the cell while increasing the photogenerated current, thus contributing to the commercial application of solar cells.
[0011] In some embodiments of the present invention, the ratio of AEEA to deionized water is 2.0 mL: 5.0 mL; the N2 purging time is 20 min; the hydrothermal treatment temperature is 160-200 °C; and the reaction time is 10 h.
[0012] In one aspect, the present invention provides a solar cell including an electron transport layer, wherein the electron transport layer is an electron transport layer obtained by the above preparation method and is composed of an organosilicon quantum dot electron transport layer material, and the thickness of the electron transport layer is 2-10 nm.
[0013] In some embodiments of the present invention, the solar cell device structure comprises, in sequence: a cathode substrate layer, an electron transport layer, an organic photoactive layer, a hole transport layer, and a metal anode layer.
[0014] In some embodiments of the present invention, the organic photoactive layer is prepared by one of the following methods: spin coating, spray coating, roll coating, spray pyrolysis, or inkjet coating.
[0015] In some embodiments of the present invention, the organic photoactive layer is specifically a thin film layer with a thickness between 100-300 nm, consisting of a bulk heterojunction structure composed of an electron donor material and an electron acceptor material; wherein the electron donor material includes polyvinyl alcohol aromatic polymers, oligothiophenes, polybenzodithiophenes homopolymers or copolymers; and the electron acceptor material includes various fullerene molecules and their derivatives or non-fullerene organic small molecules and their derivatives.
[0016] Furthermore, in some embodiments of the present invention, the electron donor material is PM6 and the acceptor material is Y6, with the molecular structure shown below:
[0017]
[0018] In some embodiments of the present invention, the cathode substrate layer includes a transparent substrate layer and a transparent conductive cathode; the transparent substrate layer is selected from one of glass covered with a conductive material or a flexible plastic film thereof, and the transparent conductive cathode is selected from a film made of indium-doped tin oxide film, fluorine-doped tin oxide film, aluminum-doped tin oxide film or a transparent metal network electrode.
[0019] Preferably, the hole transport layer material is selected from molybdenum oxide thin films, nickel oxide thin films, vanadium oxide thin films, or oxide thin films and their corresponding metal sulfide salt thin films;
[0020] Preferably, the metal anode layer is selected from silver, aluminum, copper, gold, graphene and its derivatives.
[0021] In another aspect, the present invention provides a method for preparing a solar cell, the preparation steps of which are as follows:
[0022] S1. The organosilicon quantum dot electron transport layer material with a concentration of 1.1 mg / ml is coated onto the cathode substrate by any of the following methods: spin coating, spray coating, roller coating, spray pyrolysis, LB film, inkjet method, or immersion, to form an electron transport layer without the need for thermal annealing.
[0023] S2. Prepare an organic photoactive layer on the electron transport layer obtained in step 1;
[0024] S3. A hole transport layer is prepared on the organic photoactive layer by spin coating or high vacuum evaporation.
[0025] S4. After preparing the hole transport layer, prepare the metal anode layer in a high-vacuum thermal evaporation chamber to obtain the solar cell.
[0026] In some embodiments of the present invention, the cathode substrate selected in step S1 is treated with ultraviolet light and ozone to improve the coating.
[0027] The advantages of this invention are:
[0028] The organosilicon quantum dot material OSiNDs-AEEA provided by this invention, as an electron transport layer material, can significantly improve carrier transport capability. It can be prepared by hydrothermal method without thermal annealing, has low material cost, low equipment requirements, and is simple and easy to implement. When the obtained material is applied to solar cells, the surface energy can be adjusted, which can significantly improve carrier transport capability. Its terminal functional group, the amino group of 3-aminopropyltrimethoxysilane (AEEA), can ensure its good solubility in water. By passivating the surface adsorbed oxygen defects, it effectively suppresses the light immersion effect of inverted organic solar cells, which helps to improve the photoelectric conversion efficiency of the cell on the basis of increasing the photogenerated current. The storage efficiency of the device is also improved, which is conducive to the commercial application of solar cells. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the structure of an organic solar cell according to an embodiment of the present invention.
[0030] Figure 2 The following are the UV-vis and fluorescence emission spectroscopy results of an embodiment of the organosilicon quantum dot OSiNDs-AEEA material of the present invention.
[0031] Figure 3 This is a transmission electron microscope image of organosilicon quantum dots OSiNDs-AEEA according to an embodiment of the present invention.
[0032] Figure 4 This is a current density-voltage characteristic curve of the organic solar cells in Application Example 1 and the comparative example of the present invention under standard test conditions. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings, but this does not constitute a limitation on the scope of protection of the present invention.
[0034] In the description of this invention, unless otherwise explicitly defined, terms such as heating, cleaning, and weighing should be interpreted broadly. Those skilled in the art can reasonably determine the specific meaning of the above terms in this invention in conjunction with the specific content of the technical solution.
[0035] In the description of this invention, references to terms such as "some embodiments" and "examples" indicate that the specific methods or materials described in connection with that embodiment or example are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiments or examples. Furthermore, the specific methods and materials described may be combined in any suitable manner in one or more embodiments or examples.
[0036] The materials used in the examples were sourced as follows: ITO conductive glass (9-15Ω / sq) and cleaning agent were purchased from Wuhu Jinghui Electronics Technology Co., Ltd.; organic molecules PM6 and Y6 were purchased from Shenzhen Ruixun Optoelectronic Materials Technology Co., Ltd.; AEEA was purchased from Aladdin; zinc acetate hydrate, 1-chloronaphthalene, MoO3, and aluminum granules were purchased from Sigma-Aldrich; ethanolamine and 2-methoxyethanol were purchased from Alfaesa (China) Chemical Co., Ltd.; electrode material Al was purchased from New Materials Technology Co., Ltd.; and other reagents such as ethanol, acetone, and chloroform were purchased from commercial platforms.
[0037] The electron donor material selected is PM6, and the acceptor material is Y6. The molecular structure is shown below:
[0038]
[0039] Example: Preparation of organosilicon quantum dot electron transport layer material
[0040] 3-Aminopropyltrimethoxysilane (AEEA) was dissolved in deionized water at a ratio of 2.0 mL: 5.0 mL. After stirring and purging with nitrogen, the solution was transferred to a stainless steel polytetrafluoroethylene-lined reactor and placed in an oven for hydrothermal treatment at 160°C for 10 hours. After the reaction was completed, the solution was allowed to cool naturally to room temperature to obtain highly fluorescent yellow OSiNDs-AEEA, which is the organosilicon quantum dot electron transport layer material of this invention.
[0041] Figure 2 The UV-vis test and fluorescence emission spectroscopy results of the obtained organosilicon quantum dot OSiNDs-AEEA material show that the synthesized OSiNDs-AEEA has weak ultraviolet absorption and strong fluorescence. Figure 3 The transmission electron microscope image of the obtained organosilicon quantum dots OSiNDs-AEEA shows obvious lattice diffraction.
[0042] Application Example 1:
[0043] Figure 1 This is a schematic diagram of the structure of an organic solar cell according to an embodiment of the present invention. Figure 1 As shown, the organic solar cell adopts an inverted structure. The organic solar cell structure of the present invention includes, from bottom to top: a cathode substrate layer 1, an electron transport layer 2, an organic photoactive layer 3, a hole transport layer 4, and a metal anode layer 5. The electron transport layer is composed of the organosilicon quantum dot electron transport layer material prepared in Example 1, and the thickness of the electron transport layer is 2-10 nm.
[0044] The specific preparation method of this organic solar cell includes the following steps:
[0045] (1) Mark the substrate composed of a transparent substrate layer and a transparent conductive cathode ITO and then clean it. The ITO coated glass substrate is ultrasonically cleaned with acetone, detergent, deionized water and ethanol in sequence, once every 15 minutes; then put it in an 80℃ oven to dry for later use.
[0046] (2) Spin-coating a solution of electron transport layer material with a concentration of 1.1 mg / mL obtained in Example 1 onto the surface of transparent conductive cathode ITO with spin-coating parameters of 2500 rpm and 30 s; no annealing is required after spin-coating to prepare ITO / OSiNDs-AE cathode interface layer, which is then transferred to a glove box in a nitrogen atmosphere.
[0047] (3) Spin-coating an organic photoactive layer PM6:Y6 onto the cathode buffer layer; wherein the mass fraction ratio of PM6 to Y6 is 1:1.2, the spin-coating parameters are 2200 rpm, 40 s, and 100 nm thickness.
[0048] (4) Anode buffer layer MoO3 is deposited on the organic photoactive layer by vapor deposition. 10nm);
[0049] (5) Evaporate metal anode Al on the anode buffer layer. 100nm).
[0050] Application Example 2
[0051] An organic solar cell, differing from Example 1 in that the concentration of the OSiNDs-AEEA solution is 0.8 mg / ml.
[0052] Application Example 3
[0053] An organic solar cell, differing from Example 1 in that the concentration of the OSiNDs-AEEA solution is 1.3 mg / ml.
[0054] Application Example 4
[0055] An organic solar cell, differing from Example 1 in that the concentration of the OSiNDs-AEEA solution is 3.2 mg / ml.
[0056] Comparative Example
[0057] A comparative example was prepared using ZnO, currently the most efficient cathode interface material for flip-chip solar cells. Specifically:
[0058] (1) Mark the substrate composed of a transparent substrate layer and a transparent conductive cathode ITO and then clean it. The ITO coated glass substrate is ultrasonically cleaned with acetone, detergent, deionized water and ethanol in sequence, once every 15 minutes; then put it in an 80℃ oven to dry for later use.
[0059] (2) Place the ITO glass in a plasma processor for treatment, then spin coat the prepared zinc acetate solution onto the ITO, and anneal at 200°C for 1 hour to completely hydrolyze it to produce a zinc oxide layer.
[0060] (3) Spin-coating an organic photoactive layer PM6:Y6 onto the zinc oxide layer; wherein the mass fraction ratio of PM6 to Y6 is 1:1.2, the spin-coating parameters are 2200 rpm, 40 s, and 100 nm thickness.
[0061] (4) Anode buffer layer MoO3 is deposited on the organic photoactive layer by vapor deposition. 10nm);
[0062] (5) Evaporate metal anode Al on the anode buffer layer. 100nm).
[0063] The final result was a comparative ZnO solar cell with the structure ITO / ZnO / PM6:Y6 / MoO3 / Al.
[0064] All preparation processes in the application examples and comparative examples were carried out in a glove box with a nitrogen inert atmosphere.
[0065] Performance testing
[0066] Organic solar cells prepared in Application Examples 1-4 and the comparative examples were tested under standard test conditions (AM1.5, 100mW / cm²). 2 The test was conducted, and the results are shown in Table 1.
[0067] Table 1. Performance Testing of Organic Solar Cells
[0068]
[0069] The results above show that, compared with the reference device, the solar cell device synthesized using the organosilicon quantum dot OSiNDs-AEEA of this invention exhibits significantly improved voltage and current, indicating that this material can effectively enhance charge transport capability and reduce bimolecular recombination. Specifically, it is observed that when the concentration of OSiNDs-AEEA in spin-coating Example 3 is 1.3 mg / ml, the device with OSiNDs-AEEA as the cathode interface shows a significant improvement in short-circuit current density and energy conversion efficiency. The improvements are most pronounced in Examples 1 and 2, where the photoelectric conversion efficiency increases from 14.84% to 15.45% and 15.30% respectively, representing increases of 4.1% and 3.1%; the short-circuit current density increases from 24.70 mA / cm². 2 They were increased to 25.44 and 25.48 mA / cm, respectively. 2 The improvements were 3% and 3.2%, respectively. However, when implementing Example 4 with spin-coating OSiNDs-AEEA (3.2 mg / ml), the energy conversion efficiency not only did not improve but actually decreased to some extent. Therefore, controlling the concentration of OSiNDs-AEEA at the interface is crucial to the device performance. When using OSiNDs-AEEA (1.1 mg / ml) as in Example 1, the carrier transport capability is significantly improved while the series resistance is reduced, resulting in an increase in FF, manifested as an improvement in current density and fill factor.
[0070] Figure 4 These are the current density-voltage characteristic curves of the organic solar cells in Example 1 (optimal concentration) and the comparative example under standard test conditions. Figure 4 As shown, Example 1 has significantly better electrical performance compared to the comparative example.
[0071] Moreover, compared with the scheme disclosed in Chinese patent CN111799379A, and compared with the electron transport layer prepared by the ultra-small organosilicon quantum dot nanomaterial OSiND according to the method reported in the literature (NanoLett.2018, 18, 1159-1167), the organic solar cell made of OSiNDs-AEEA material in this application not only has a significantly increased short-circuit current, but also a significant improvement in fill factor and conversion efficiency.
[0072] This application proposes an improved method for preparing silicon quantum dot materials. It utilizes a hydrothermal reaction of 3-aminopropyltrimethoxysilane (AEEA) with deionized water under nitrogen purging to prepare OSiNDs-AEEA material. This method is simple, feasible, and requires no thermal annealing, resulting in low material cost. When applied to solar cells, the material exhibits adjustable surface energy and significantly improved carrier transport capability. Specifically, the amino group at the end of the material—the amino moiety of 3-aminopropyltrimethoxysilane (AEEA)—ensures good solubility in water. By passivating surface adsorbed oxygen defects, it effectively suppresses the light immersion effect in inverted organic solar cells, contributing to increased photoelectric conversion efficiency while enhancing photocurrent. The storage efficiency of the device is further improved. The material can be spin-coated into a film for solar cell fabrication, resulting in low material cost and eliminating the need for additional doping and thermal annealing. The method is simple and feasible, requiring minimal equipment and further improving the device's current density, fill factor, and storage efficiency, thus facilitating the commercial application of solar cells.
[0073] Obviously, the embodiments described above are merely some embodiments of the present invention, and not all embodiments. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this invention should be included within the protection scope of this invention. Therefore, the protection scope of this invention should be determined by the scope of the claims.
Claims
1. A solar cell, comprising an electron transport layer, characterized in that, The electron transport layer is composed of an organosilicon quantum dot electron transport layer material, which is prepared by the following steps: 3-aminopropyltrimethoxysilane is dissolved in deionized water, stirred, and nitrogen is introduced, followed by hydrothermal treatment. After the reaction is completed, the mixture is naturally cooled to room temperature to obtain the organosilicon quantum dot electron transport layer material OSiNDs-AEEA; the ratio of 3-aminopropyltrimethoxysilane to deionized water is 2.0 mL: 5.0 mL; the nitrogen purging time is 20 min; the hydrothermal treatment temperature is 160-200℃, and the reaction time is 10 h. The thickness of the electron transport layer is 2-10 nm.
2. The solar cell according to claim 1, characterized in that, The solar cell structure comprises, in sequence: a cathode substrate layer, an electron transport layer, an organic photoactive layer, a hole transport layer, and a metal anode layer.
3. The solar cell according to claim 2, characterized in that, The organic photoactive layer is prepared by one of the following methods: spin coating, spray coating, roll coating, spray pyrolysis, or inkjet printing.
4. The solar cell according to claim 2, characterized in that, The organic photoactive layer is specifically a thin film layer with a thickness between 100-300 nm, consisting of a bulk heterojunction structure composed of electron donor materials and electron acceptor materials; wherein the electron donor materials include polyvinyl alcohol aromatic polymers, oligothiophenes, polybenzodithiophenes homopolymers or copolymers; and the electron acceptor materials include various fullerene molecules and their derivatives or non-fullerene organic small molecules and their derivatives.
5. The solar cell according to claim 4, characterized in that, The selected electron donor material is PM6, and the acceptor material is Y6. The molecular structure is shown below: 。 6. The solar cell according to claim 2, characterized in that, The cathode substrate layer includes a transparent substrate layer and a transparent conductive cathode; the transparent substrate layer is selected from one of glass covered with a conductive material or a flexible plastic film thereof, and the transparent conductive cathode is selected from films made of indium-doped tin oxide films, fluorine-doped tin oxide films, aluminum-doped tin oxide films or transparent metal network electrodes.
7. The solar cell according to claim 6, characterized in that, The hole transport layer material is selected from molybdenum oxide thin films, nickel oxide thin films, vanadium oxide thin films, or sulfide metal salt thin films corresponding to the above oxide thin films.
8. The solar cell according to claim 6, characterized in that, The metal anode layer is selected from silver, aluminum, copper, gold, graphene and its derivatives.
9. The method for preparing a solar cell according to any one of claims 1 to 8, wherein the preparation steps are as follows: S1. The organosilicon quantum dot electron transport layer material at a concentration of 1.1 mg / ml is coated onto the cathode substrate by any one of the following methods: spin coating, spray coating, roller coating, spray pyrolysis, LB film, inkjet printing, or immersion, to form an electron transport layer without the need for thermal annealing. S2. An organic photoactive layer is prepared on the electron transport layer obtained in step S1; S3. A hole transport layer is prepared on the organic photoactive layer by spin coating or high vacuum evaporation. S4. After preparing the hole transport layer, prepare the metal anode layer in a high-vacuum thermal evaporation chamber to obtain the solar cell.
10. The method for preparing a solar cell as described in claim 9, characterized in that, The cathode substrate selected in step S1 has been treated with ultraviolet light and ozone.
Citation Information
Patent Citations
Solar cell containing organic silicon quantum dot material and preparation method thereof
CN111799379A
Method for preparing water-soluble fluorescent silicon quantum dots by using hydrothermal process
CN103896271A